PENYULUHAN PENCEGAHAN MENIKAH USIA ANAK DI KECAMATAN CURUG KOTA SERANG - Rika Kartika; Gatot Hartoko; Iis Nurasiah (Jurnal Abdimas Bina Bangsa, 2021)
Marriage that occurs at the age of a child is one of the national problems, in Indonesia. The rate of child marriage in Indonesia is quite high. Children are allowed to marry both male and female with a minimum age of 19 years. However, the age of 19 is still a teenager which is too early to decide to get married because he has not been able to control himself well. Based on data from the 2014 BKKBN in Banten Province, 6.5% of women married at the age of children, namely under the age of 15 years. In Cibeo Village which is one of the villages in Curug District, it shows that there are 62.2% of women who married at the age of children from 45 samples. Child marriage has an impact on the health of the child, both physically and psychologically. This community service aims to provide education to the community in Curug District, such as Kemanisan, Pancalaksana, and Tinggar Villages, regarding child marriage. The education provided uses the extension method through online penyuluhan secara virtuals, using the zoom meeting platform. The existence of counseling on prevention of marriage at a child's age is able to open a mindset, add insight and knowledge related to marriage at a young age so that the Curug community, especially teenagers, can consider before making a decision to marry at a child's age